STUDI FILTRASI AIR BELIMBING WULUH SEBAGAI ELEKTROLIT BATERAI PENGGANTI ELEKTROLIT H2SO4 - Moranain Mungkin; Denny Akbar Tanjung (Program Studi Kimia - Universitas Sari Mutiara Indonesia, 2019)
Research has been conducted about the study of wuluh starfruit water filtration as a battery electrolyte replacement for H2SO4 electrolytes. During this time the battery electrolyte used H2SO4. While H2SO4 causes itching and sores, it is even toxic to the body when inhaled, so in this research an experiment was conducted to replace electrolyte batteries from vegetable materials, namely using wuluh starfruit water filtration (WSWF). The purpose of this study is to make an environmentally friendly electrolyte alternative. The results showed that the use of battery electrolytes from wuluh starfruit water filtration (WSWF) turned out to be able to react with the battery anode and cathode to produce an electrical voltage of 7.13 volts and an electrical current of 0.56 mA/15 minutes with a light testing load of 12V/5W. The results of this study will be further developed so that it can improve the electrical characteristics of the WSWF electrolyte which is identical to the H2SO4 electrolyte.